ANALISIS UJI-T BERPASANGAN UNTUK MELIHAT PENGARUH PEMBINAAN OLIMPIADE MATEMATIKA DALAM MENINGKATKAN KEMAMPUAN SISWA - Idhia Sriliana; Jose Rizal; Baki Swita; Pepi Novianti; Etis Sunandi (Universitas Bengkulu, 2018)
SMA Negeri 3 Bengkulu city is one of the active participants in the competition OSN SMA/MA in Bengkulu. But the school's achievements have not been prominent, especially in the field of Mathematics. In the period of last 10 years, SMAN 3 Bengkulu have never gotten quite encouraging achievement in Maths OSN. Department of Mathematics, University of Bengkulu has the human resources pretty promising, that competent teaching staff to improve the ability of reasoning and analysis of students SMA Negeri 3 Bengkulu City through guidance materials OSN Mathematics SMA/MA. Therefore, it will be held activities in the promotion of students regarding the material OSN Mathematics SMA/MA to improve the ability of reasoning and analysis of students so that they know how concepts and strategies work on the problems OSN Mathematics SMA/MA with reasoning and analysis are correct, so as to achievement on activities OSN Mathematics both at the provincial and national levels. After coaching is done, using paired t-test analysis can be concluded that these activities have a significant influence. Development activities that have been implemented can increase the ability of reasoning and analysis of the students as well as students of SMAN 3 of Bengkulu in adding knowledge on mathematics material and questions in SMA/MA OSN. Keywords: OSN Mathematics, SMAN 3 Bengkulu, Paired t-test